2021
DOI: 10.3389/fvets.2021.676896
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Rickettsia Species in Small Ruminant Ticks From Tunisia

Abstract: Tick-borne rickettsioses present a significant public health threat among emerging tick-borne diseases. In Tunisia, little is known about tick-borne Rickettsia pathogens. Therefore, the aim of this study was to investigate the presence of Rickettsia species in small ruminant ticks from Tunisia. Adult ticks (n = 694) were collected from goats and sheep in northern Tunisia. Obtained ticks were identified as Rhipicephalus turanicus (n = 434) and Rhipicephalus sanguineus sensu lato (n = 260). Selected ticks (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…cornupunctata ticks infesting cattle, buffaloes, sheep, and goats were found to be positive for R. massiliae . Previously, R. massiliae has been detected in tick species of the genera Rhipicephalus , Haemaphysalis , Hyalomma , and Dermacentor , collected from dogs, small ruminants, and cattle in China, Iran, Nigeria, Tunisia, Portugal, Argentina, and the USA [ 17 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Rickettsia massiliae in Rh.…”
Section: Discussionmentioning
confidence: 99%
“…cornupunctata ticks infesting cattle, buffaloes, sheep, and goats were found to be positive for R. massiliae . Previously, R. massiliae has been detected in tick species of the genera Rhipicephalus , Haemaphysalis , Hyalomma , and Dermacentor , collected from dogs, small ruminants, and cattle in China, Iran, Nigeria, Tunisia, Portugal, Argentina, and the USA [ 17 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Rickettsia massiliae in Rh.…”
Section: Discussionmentioning
confidence: 99%
“…conorii, R. conorii subsp. israelensis, R. aeschlimannii, R. sibirica mongolitimonae, R. massiliae, R. slovaca, R. raoultii, and R. monacensis (81,84,125,181). In Algeria, both R. conorii subsp.…”
Section: North Africamentioning
confidence: 99%
“…sanguineus s.l. ticks collected from livestock in Tunisia (70,84,197), Morocco (103), and Algeria (67). Similarly, R. monacensis DNA was detected in Rh.…”
Section: North Africamentioning
confidence: 99%
“…The genus Rickettsia is classified into four groups: spotted fever group (SFG), typhus group (TG), transitional group (TRG), and ancestral group (AG). To date, more than 30 species and subspecies have been reported worldwide with several of these (SFG, TG) circulating in domestic and wild mammals (Belkahia et al, 2021; Selmi et al, 2021), and approximately one‐half to two‐thirds of these species have been confirmed as human pathogens (Faccini‐Martinez et al, 2014). As vector‐borne pathogens that are mainly transmitted to humans and other animals through arthropods, the common vectors of this genus include ticks, fleas, and mites.…”
Section: Introductionmentioning
confidence: 99%